Risk factors for carbapenem‐resistant Klebsiella pneumoniae bloodstream infection among rectal carriers: a prospective observational multicentre study. (11th August 2014) - Giannella, M.; Trecarichi, E. M.; De Rosa, F. G.; Del Bono, V.; Bassetti, M.; Lewis, R. E.; Losito, A. R.; Corcione, S.; Saffioti, C.; Bartoletti, M.; Maiuro, G.; Cardellino, C. S.; et al.
Abstract Knowledge of carbapenem‐resistant Klebsiella pneumoniae (CR‐KP) colonization is important to prevent nosocomial spread but also to start prompt adequate antibiotic therapy in patients with suspicion of infection. However, few studies have examined the incidence and risk factors for CR‐KP bloodstream infection (BSI) among rectal carriers. To identify risk factors for CR‐KP BSI among carriers, we performed a multicentre prospective matched case–control study of all adult CR‐KP rectal carriers hospitalized in five tertiary teaching hospitals in Italy over a 2‐year period. Carriers who developed CR‐KP BSI were compared with those who did not develop subsequent BSI. Overall, 143 CR‐KP BSIs were compared with 572 controls without a documented infection during their hospitalization. Multivariate analysis revealed that admission to the Intensive Care Unit (ICU) (OR, 1.65; 95% CI, 1.05–2.59; p 0.03), abdominal invasive procedure (OR, 1.87; 95% CI, 1.16–3.04; p 0.01), chemotherapy/radiation therapy (OR, 3.07; 95% CI, 1.78–5.29; p <0.0001), and number of additional colonization sites (OR, 3.37 per site; 95% CI, 2.56–4.43; p <0.0001) were independent risk factors for CR‐KP BSI development among CR‐KP rectal carriers. A CR‐KP BSI risk score ranging from 0 to 28 was developed based on these four independent variables. At a cut‐off of ≥2 the model exhibited a sensitivity, specificity, positive predictive value and negative predictive value of 93%, 42%, 29% and 93%, respectively. Colonization at multiple sites with CR‐KP was the strongest predictor of BSI development in our large cohort of CR‐KP rectal carriers.